Crackproof your software : the best ways to protect your software against crackers - Červeň, Pavol, 1976- (No Starch Press, 2002)
This essential resource for software developers highlights the weak points in "well-protected" software, shows how crackers break common protection schemes, and how to defend against crackers. Includes in-depth discussions of anti-debugging and anti-disassembling. The CD-ROM contains compression and encoding software, debuggers and anti-debugging tricks, practical protection demonstrations, and extended examples from the book.